Integration of Positive Language in Hypnoteaching Modules: Solutions to Increase the Learning Motivation of Elementary School Students (Study at MIN 2 Tegal) - Aziz, Aminudin; Agung, Nugraha Rahmad; Suriswo, Suriswo (Journal of English Language and Education, 2025)
This study aims to develop a teaching module guidebook based on hypnoteaching and positive language as an affective learning strategy to improve student motivation at Madrasah Ibtidaiyah Negeri (MIN) 2 Kota Tegal. The research is motivated by the low learning motivation among fifth-grade students, as indicated by limited engagement, low affective expression, and challenges faced by teachers in creating an enjoyable classroom atmosphere. The research employed a Research and Development (RD) approach based on the Borg Gall model. Data were collected through observation, interviews, learning motivation questionnaires, and expert validation and product effectiveness tests. The findings reveal that prior to using the module, most students were in the low to moderate motivation categories. The developed guidebook integrates principles of hypnoteaching, including affirmation, relaxation, visualization, and the use of suggestive and affirmative language. Validation and effectiveness tests showed that the module is highly feasible and effective in enhancing student learning motivation. Therefore, this module offers a practical and inspiring solution for teachers in designing empowering, communicative, and affective-centered learning.